Life Cycle–Based Evaluation of Sustainable Infrastructure within Civil Engineering Frameworks - Ming Sheng Fang (Advanced Business Journal, 2025)
The construction sector contributes nearly 39% of global carbon emissions, making it a critical focus area for sustainable transformation. This study explores how integrating Circular Economy (CE) principles into civil engineering can promote environmental and economic sustainability. Emphasis is placed on the utilisation of industrial byproducts—specifically steel slag and fly ash—as partial replacements for cement and natural aggregates in concrete. Laboratory experiments assessed the mechanical and durability performance of these mixes, while Life Cycle Assessment (LCA) and cost–benefit analyses quantified their environmental and economic impacts. Results indicate that CE-based concrete formulations can reduce embodied carbon by up to 30% and material costs by 10–15%, without compromising strength or durability. Furthermore, a Circular Business Model Framework was developed to guide construction firms in implementing CE strategies that balance profitability with sustainability goals. This research demonstrates that circular material use not only enhances structural performance but also establishes sustainable infrastructure as a viable strategic business model for the future built environment.